A Molecular Dynamics-Based Approach to Study the Effect of Covalently Bonded Modified Graphene on the Heat Transport Properties of Graphene/Natural Rubber Composite Material Interfaces - Yan, Yeqi (Langmuir : the ACS journal of surfaces and colloids, 2024)
Due to its excellent thermal conductivity, graphene can have great potential in the thermal conductivity of rubber composites. However, the interfacial thermal resistance between graphene and rubber severely hinders this application. In this work, molecular dynamics methods were used to study the interfacial thermal transport of carboxylated, aminated, hydroxylated, and oxy-bridged graphene in rubber composites. The results showed that the covalently bonded modified graphene significantly improved the thermal conductivity of the composites, with increases in thermal conductivity of 156.56%, 86.83%, 60.71%, and 44.28% and decreases in interfacial thermal resistance of 41.84%, 34.72%, 31.86%, and 16.74%, respectively. By calculating the phonon densities of states of different functionalized graphenes, it was found that covalently bonded functional groups increased the phonon match between graphene and natural rubber. However, when the degree of functionalization was greater than 11.96%, the phonon match was maintained at a stable value, which was why the covalently bonded modified graphene could significantly reduce the interfacial thermal resistance. Moreover, the graphene modified by covalent bonding was more uniformly distributed inside the natural rubber. The results of this study provide important theoretical guidance for preparing graphene/natural rubber composites with high thermal conductivity